2022
DOI: 10.1109/jestpe.2019.2928478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Solder Degradation on V CE of IGBT Module: Experiments and Modeling

Abstract: Solder degradation is one of the main packaging failure modes in insulated gate bipolar transistor (IGBT) modules, which is usually evaluated through the change of thermal resistance. However, due to the strong electro-thermal coupling in IGBT module, solder degradation also affects electrical characteristics, such as on-state voltage VCE. The impact mechanism of solder degradation on VCE is analyzed in this paper firstly. For the study of the solder degradation independently, a press-packing setup is designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The time until failure is often several weeks long, and the module is tested at several stressor levels to map its influence on the lifetime [39]. With the improvement in simulation software packages and the increase in computing power, it increases the viability of using the software tools to assess individual failure modes and reliability issues of power module packages [19]- [21].…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The time until failure is often several weeks long, and the module is tested at several stressor levels to map its influence on the lifetime [39]. With the improvement in simulation software packages and the increase in computing power, it increases the viability of using the software tools to assess individual failure modes and reliability issues of power module packages [19]- [21].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Alternatively, the problems related to thermomechanical induced stress are evaluated digitally using FEM software. Predicting the location and amount of thermomechanical stress in the module is important to aid in the improvement of the reliability of future power modules designs [19]- [21]. Setting up a FEM model of a power module often requires complex 3D modelling, knowledge of mixed boundary conditions and a library of material properties, which all can be linked to some degree of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…V CE-on is an important characteristic parameter for condition monitoring [28]. Generally, a 5% increase of V CE-on is taken as a failure standard [29]. A power cycling test of a single-chip module was carried out by Jiang et al and the V CE-on variation as shown in Figure 2b was obtained.…”
Section: Fretting Wear Degradationmentioning
confidence: 99%
“…Mainly, if the change in collector-emitter voltage (V CE ) or thermal resistance (R th ) exceeds a certain limit (e.g., 5-20% [30]), it indicates a failure/fracture in the IGBT. According to [31], a slight change in the initial collector-emitter voltage was observed due to the solder lead degradation by comparing a new IGBT with an aged IGBT. The threshold gate voltage (V GE_th ) may also vary during the degradation process, which can disrupt normal switching characteristics and reduce the operating frequency [32].…”
Section: Introductionmentioning
confidence: 99%
“…They found that fracture/cracks in the bond wires would increase this voltage. Jia et al [31] investigated the impact of solder layer degradation on the V CE voltage. They claimed that the solder degradation will cause an increase in operating temperature, which can change the electrical (V CE ) and thermal (junction-to-case thermal resistance R th(j-c) ) characterizations of the IGBT over time.…”
Section: Introductionmentioning
confidence: 99%